2010
DOI: 10.1021/ma101943k
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Structure of β-Cyclodextrin and Poly(ethylene oxide)-block-poly(propylene oxide)-block-poly(ethylene oxide) Inclusion Complexes

Abstract: Supramolecular crystals were prepared via self-assembly of a series of inclusion complexes of β-cyclodextrin (β-CD) with poly(ethylene oxide)-block-poly(propylene oxide)-block-poly(ethylene oxide) (PEO-b-PPO-b-PEO) block copolymer. In this study, two PEO-b-PPO-b-PEO copolymers were used with different molecular weights for the PEO blocks. On the basis of two-dimensional (2D) wide-angle X-ray diffraction (WAXD) and selected area electron diffraction (SAED) experiments, the supramolecular crystal structure was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…Early papers have reported polyrotaxane nanoparticles as drug carriers, however, the selfassembly of polyrotaxane nanoparticles were driven by the crystallization of polyrotaxanes [12][13][14], whose compact architectures hindered the loading of anticancer drugs. In our previous work, we reported a new strategy, small π-π conjugated molecules such as coumarin derivative and cinnamic acid were immobilized on the terminal groups of PEG chains to prepare amphiphiles [15,16], α-cyclodextrins (α-CDs) were threaded in the amphiphiles and the polyrotaxanes self-assembled into nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Early papers have reported polyrotaxane nanoparticles as drug carriers, however, the selfassembly of polyrotaxane nanoparticles were driven by the crystallization of polyrotaxanes [12][13][14], whose compact architectures hindered the loading of anticancer drugs. In our previous work, we reported a new strategy, small π-π conjugated molecules such as coumarin derivative and cinnamic acid were immobilized on the terminal groups of PEG chains to prepare amphiphiles [15,16], α-cyclodextrins (α-CDs) were threaded in the amphiphiles and the polyrotaxanes self-assembled into nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, these precipitates are formed by the inclusion of the PPO blocks inside the β-CD cavities producing a polypseudorotaxane type structure (Harada, 1998) yielding self-associated structures such as nanoplatelets (Perry et al, 2011, Tsai et al, 2010.…”
Section: Resultsmentioning
confidence: 99%
“…This can be very useful for some applications such as drug release resulting from a complete erosion of the matrix. Recently, some studies have demonstrated the self-organization of Pluronic/natural β-CD systems in crystalline domains [21][22][23][24] . These studies prove that a complex with a certain crystalline order is obtained when combining PEO-PPO-PEO block copolymers with β-CD.…”
Section: Introductionmentioning
confidence: 99%